2003
DOI: 10.1210/jc.2002-021413
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally High Expression of Proteasome Activator-γ in Thyroid Neoplasm

Abstract: PA28-gamma is the activator of 20S proteasome, the ATP-dependent proteolytic system that plays an important role in cell cycle progression in various cell types. In this paper, we show the abnormally high expression of PA28-gamma in various thyroid neoplasms. Thyroid samples were obtained from patients with normal thyroid (4 cases) and with the following diseases: papillary adenocarcinoma (13 cases), multinodular goiter (4 cases), and anaplastic carcinoma (1 case). PA28-gamma expression was estimated by immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
49
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 42 publications
3
49
1
Order By: Relevance
“…This finding is in agreement with a recent study that showed increased expression of PA28γ protein during cancer progression and its correlation with PCNA labeling index (19). Thus, the results suggest the possible involvement of PA28γ in HCC progression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in agreement with a recent study that showed increased expression of PA28γ protein during cancer progression and its correlation with PCNA labeling index (19). Thus, the results suggest the possible involvement of PA28γ in HCC progression.…”
Section: Discussionsupporting
confidence: 93%
“…These results are contradictory to those from other studies on other types of cancer, such as thyroid carcinoma; the nuclear PA28γ level was higher in these tumors compared to non-tumor tissues (19). While the exact reason for Table II.…”
Section: Discussioncontrasting
confidence: 80%
“…Indeed, studies indicated that REGγ is absent in breast cancers but upregulated in thyroid cancers. 7,45 Our study revealed that the oncoprotein c-Myc is a novel substrate of REGγ. We found that c-Myc protein is negatively regulated by REGγ in several cancer cell lines, including HeLa, MCF7 and MEFs.…”
Section: Discussionmentioning
confidence: 78%
“…Increasing evidence has also suggested that overexpressed REGγ could positively contribute to cell cycle progression in the development of various human cancers. For instance, REGγ has been reported to be highly expressed in thyroid cancer (Okamura et al, 2003) and in colorectal cancer serum (Roessler et al, 2006). Recently, the overexpressed REGγ has been also found in human breast cancer cells and the metastatic lymph nodes (Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%